PENGARUH PEMBELAJARAN KOOPERATIF MELALUI MEDIA PERMAINAN ULAR TANGGA TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN IPS DI SEKOLAH DASAR - Sari, Maya Kartika (Premiere Educandum, 2015)
Learning social studies in elementary dominated by the monotonous teaching methods, conventional and less effective, the teacher dominated learning, teaching by lecturing andrecorded material, and using instructional media. This needs to be an improvement oflearning. Researchers trying to implement cooperative learning methods through the mediagame of snakes and ladders as an attempt to create learning interesting, active, and canmotivate student learning. This study aims to determine the effect of cooperative learningthrough the media cooperative game of snakes and ladders on learning outcomes of fourthgrade students in academic year 2014/2015 Tembi Bantul. The study population was allstudents in fourth grade Tembi as experimental class and fourth grade students Bangeran asthe control class. The samples were overall Tembi fourth grade students were 22 students andfourth grade students Bangeran as many as 11 students. This study design used quantitativeresearch methods. Collecting data in this study used the test method. The test method used isthe pre-test and post-test were given to the experimental group and the control group.Analysis of the data used is a statistical method t test (t-test). Results of the data analysis t testÂ (t-test) obtained value = 12.7754. At the significance level (Î±) = 0.05 earned value = 2.0441.Then thitungÂ â¥ tÂ tabeÂ is 12,7754 â¥ 2,0441, then Ho is rejected and Ha accepted. The conclusion ofÂ this study was the influence of cooperative learning through the medium of snakes andladders game on learning outcomes of students Subjects IPS in Tembi Bantul elementaryschool year 2014/2015.Keywords : Cooperative Model, Media Snakes and Ladders, Learning Outcomes